INFLUENCE OF LEADERSHIP AND WORK MOTIVATION TOWARD TEACHER PERFORMANCE IN JUNIOR HIGH SCHOOL ANGKASA ASTRA KSETRA - Nuraeni .; Epi Parela (University of Sang Bumi Ruwa Jurai, 2020)
The purpose of this study was to study leadership and work motivation towards teacher performance in SMP Angkasa Astra Ksetra, Tulang Bawang Regency. This type of research includes the type of quantitative descriptive research, the explanation of this research results in making systematic, factual, and accurate reports about facts and facts. This study used 22 research respondents. There are three variables in this study, namely: 2 (two) Independent variables (Xi and X) and 1 (one) variable that supports leadership (Xi) and work motivation (X) as independent variables and Gum (Y) performance as supported variables. From the results of data processing, the following hypotheses have been found. There is the influence of leadership (Xi) on teacher performance (Y), with a level of influence (R-square) of 81.3%. Related to work motivation (X) to teacher performance (Y), with a level of influence of 90.3%. With the influence of leadership (Xi), work motivation (X) with teacher performance (Y), with an influence level of 90.6%.